The Untouchable Muslim: A Preliminary Discussion of the Bede Community in Bangladesh - Muenuddin, Muhammad; Islam, Arshad (Advances in Social Sciences Research Journal, 2022)
This paper examines the present socio-economic and educational status of the Bede (“untouchable”) minority community in Bangladesh. Despite belonging to the Islamic faith, Bedes are not generally welcomed in mainstream Muslim society. They are primarily nomadic, and live by selling folk remedies and snake charming, deprived of health and educational resources, and living in great poverty. The level of literacy and health facilities for Bedes are negligible. This analysis addresses the dearth of academic studies of the Bede community, and the more serious lack of governmental and non-governmental initiatives to listen to the voice of the Bede community and meet their needs. This study recommends that the government and human rights organizations must come forward to support this community.